Continuous non-locking vs. interrupted suturing techniques for the repair of episiotomy or second-degree perineal tears: A single-blind randomized controlled trial - Faal Siahkal, Shahla; Abedi, Parvin; Iravani, Mina; Esfandiarinezhad, Parvin; Dastoorpoor, Maryam; Bakhtiari, Shahla; Najafian, Mahin; Sharifipour, Foruzan; Mohaghegh, Zaynab (Frontiers in Surgery, 2023)
Objective: Perineal trauma is a serious and frequent problem after childbirth which is experienced by millions of women worldwide. The technique used for perineal repair may have an impact on pain and wound healing. The aim of the present study was to compare the continuous non-locking technique with interrupted suturing for the repair of episiotomy or second-degree perineal tears. Methods: A single-blind randomized-controlled trial was conducted from October 2021 to August 2022 in Sina Hospital, Ahvaz, Iran. Three hundred women were selected and randomly assigned into control and intervention groups using block randomization technique. The main outcomes included pain and wound healing that were assessed using visual analog scale (VAS), as well as redness, edema, ecchymosis/bruising, discharge, and approximation scale (REEDA). The secondary outcomes were the use of analgesics, duration of perineal repair, material used for suturing, pain during urination and defecation, and resumption of sexual intercourse. The participants were followed up on the first and seventh days and in the 6th week postpartum. Mann-Whitney, Chi-square, and Generalized Estimating Equations (GEE) model were used for data analysis. Results: Wound healing was significantly better in the continuous non-locking suture technique compared to the interrupted technique (β= -1.98; P > 0.0001). Women also experienced less pain in the continuous non-locking suture technique (β= - 2.46; P > 0.0001). There was a reduction in the use of analgesics, the duration of perineal repair, and the material used for suturing in the continuous non-locking suturing technique as opposed to the interrupted method (P <0.0001).The odds of pain during urination and defecation significantly reduced in women who underwent the continuous non–locking method (P <0.001). Also, women in the continuous non–locking group resumed their sexual intercourse earlier (P <0.0001). Conclusion: The findings of this study revealed that use of continuous non-locking technique for suturing was associated with reduced perineal pain and improved wound healing. Furthermore, it was associated with a shorter duration of perineal repair, less suture material used, and less need for analgesics compared with the interrupted method. There is, however, need for more studies to confirm the results of the present study.